ANALISIS FAKTOR – FAKTOR YANG MEMENGARUHI CADANGAN DEVISA INDONESIA - Nurul Halimah, Siti Marfuah (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
State assets in the form of foreign currency is called foreign exchange reserves and is used for various purposes, including maintaining exchange rate stability, international trade and national economic stability. The aim of this research is to ascertain how Indonesia's foreign exchange reserves are affected by imports, exports, interest rates and exchange rates between 1986 and 2022. The World Bank website provides the time series data used in this analysis. This research analyzes data using eviews 12 and the Autoregressive Distributed Lag (ARDL) approach. Exports and interest rates have no effect on foreign exchange reserves in the short or long term. Imports and exchange rate has a negative and significant influence in the short term, while in the long term it has a positive and significant influence on foreign exchange reserves.